Papua New Guinea : 2007 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion for Papua New Guinea. (IMF Staff Country Reports; Country Report, 2008)
Papua New Guinea's economic performance has strengthened since the last Article IV Consultation. The country has significant underlying vulnerabilities. The economy is exposed to commodity price shocks, and mineral production is expected to decline over the medium to longer term. However, macroeconomic vulnerabilities have intensified, in particular, the potential for higher unproductive fiscal spending to raise demand pressures and spur inflation. Prudent fiscal policies are welcomed. Implementation of the multi-donor technical assistance plan is encouraged. The authorities are encouraged to accelerate the structural reforms and improve infrastructure.